Co-regulation of multiple signaling mechanisms in pp60v-src induced closure of Cx43 Gap junction channels - Mitra, Siddhartha S. (2012)
Attenuation in gap junctional coupling has consistently been associated with induction of rapid or synchronous cell division in normal and pathological conditions. In the case of the v-src oncogene, gating of Cx43 gap junction channels has been linked to both direct phosphorylation of tyrosines (Y247 and 265) and phosphorylation of serine target of Erk1/2 (S255, 279, and 282) on the cytoplasmic C-terminal domain of Cx43. However, only the latter has been associated with acute rather than chronic gating of the channels immediately after v-src expression, a process that is mediated through a “ball and chain” type mechanism. In this study we show that while ERK1/2 is necessary for acute closure of gap junction channels, it is not sufficient. Rather, multiple pathways converge to regulate Cx43 coupling in response to expression of v-src, including parallel signaling through PKC and MEK1/2, with additional positive and negative regulatory effects mediated by PI3kinase, distinguished by the involvement of Akt.